The Structural Crisis in the Swedish Economy : Role of Labor Markets - Ramaswamy, Ramana (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1993)
This paper focuses on the main institutional features of the Swedish labor market and analyzes the reasons for the high wage inflation and slow productivity growth. The so-called Swedish model, usually identified with an advanced welfare state, has attracted attention from many quarters for its apparent earlier success. One of the distinctive features of the Swedish model has been its unique labor market institution, which combines centralized bargaining with a policy of wage equalization, designed with a view to promoting a favorable macroeconomic performance. The concept of solidaristic wages was initially conceived as equal pay for equal work. Estimates provided by the Swedish Ministry of Finance, indicate that the wage spread for industrial workers, calculated as the difference between the highest and lowest deciles in 1984, was 34 percent for Sweden in contrast to 210 percent for the United Kingdom and 490 percent for the United States.